Does farmers' entrepreneurial competencies explain their household poverty status? Evidence from rural areas of Kwara State, Nigeria - Abigail Gbemisola Adeyonu; Olubunmi L. Balogun; Ifeoluwapo O. Amao; Timothy O. Agboola (Cogent Economics & Finance, 2022)
Ending poverty in all its forms and in all places by 2030 is number one of the 17 Sustainable Development Goals (SDGs). However, in less than a decade to the time set for actualizing this goal, poverty is still pervasive in Nigeria and more endemic among farmers in rural areas. Entrepreneurship is seen as a veritable tool to alleviate poverty and stimulate economic growth in some developing countries including Nigeria. Howbeit, little is known about the relationship between farmers' entrepreneurial competencies and poverty. Thus, this study examined the effects of farmers' entrepreneurial competencies on household poverty status in rural areas of Kwara State, Nigeria. A three-stage sampling procedure was employed in selecting 272 farm households, with at least a member who was engaged in at least one other means of livelihood (enterprise). Data were collected between February and March 2019 and analysed with descriptive statistics, factor analysis, Foster, Greer, and Thorbecke (FGT) weighted poverty indices and probit regression at p = 0.05. At a daily poverty line of 1.90 (₦684.00) per capita, 55.15% of the households were poor. The findings indicate that poverty among farm households varied with their level of entrepreneurial competencies. Perseverance competence significantly increased household poverty, while social competence reduced it. The findings suggest poverty reduction strategies that come directly from farmers' own initiative and their resilience which is rural focused regardless of other challenges that may exist.
Keywords: 330; Entrepreneurial competencies; rural farmers; poverty; factor analysis; Nigeria